The effects of self-talk on anticipation responses in receiving tennis serves - Takahashi, M.; van Raalte, J. L.; Tanaka, N.; Sato, M.; Kamiwazumi, J.; Mizuochi, F. (Medicine and Science in Tennis, 2009)
The purpose of this study was to examine the effects of self-talk on anticipation responses in receiving tennis serves. Twenty four male tennis players (twelve experienced and twelve novice players) were tested in the laboratory on simple reaction time, choice reaction time, and tennis serve reaction with anticipation. For the tennis serve reaction with anticipation task, serve films were edited to show an elite tennis player from three seconds before racket-ball contact to one second after racket-ball contact. Participants were assigned to use control (i.e., normal), instructional (i.e., task-oriented or technical directions such as "focus on the center of the server"), or motivational (i.e., confidence building and effort maintaining) self-talk when viewing serves. The order of self-talk conditions was counterbalanced. For each serve shown, participants were asked to indicate the direction that they expected the serve was going (i.e., down the middle or out wide) by pushing the right or left LED button as quickly and accurately as possible. Reaction time (RT), anticipation timing (ATg), and accuracy were calculated and a 2 (experienced and novice groups) x 3 (control, instructional, and motivational self-talk conditions) repeated-measures ANOVA was conducted. The main results were as follows: 1) ATgs for both groups were prior to the racket-ball contact of serve in the reaction time paradigm. 2) There was a significant interaction between skill levels and self-talk conditions in RT (p=.001), ATg (p=.001), and accuracy (p=0.022). For the experienced group, RT and ATg in the control condition were significantly earlier than for the other conditions (p<.05). Regarding accuracy, the control condition was significantly lower than the other conditions (p<.05). For the novice group, there were no significant differences in RT, ATg, and accuracy. It was concluded that for experienced tennis players, use of instructional and motivational self-talk delayed their anticipation responses, but increased accuracy.